2020
DOI: 10.1021/acs.cgd.0c00066
|View full text |Cite
|
Sign up to set email alerts
|

An Imide-Decorated Indium-Organic Framework for Efficient and Selective Capture of Carcinogenic Dyes with Diverse Adsorption Interactions

Abstract: A functional indium-organic framework with an anionic skeleton, [(CH 3 ) 2 NH 2 ][In(BDCPPI)]•0.5DMF•H 2 O (compound 1, H 4 BDCPPI = N,N′-bis(3,5-dicarboxyphenyl)pyromellitic diimide, DMF = N,N-dimethylformamide), has been solvothermally synthesized. Compound 1 with a (4, 4)-connected pts network is constructed by negative [In(OOC) 4 ] − secondary building units (SBUs) and expanded tetracarboxylate ligands with functional imide groups. Meanwhile, the overall framework possesses large open channels of 17.3 × 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 93 publications
1
15
0
Order By: Relevance
“…The release of such materials generates unpleasant colored water as the existence of less than 1 ppm of these dyes in water is highly perceptible. Further, discharge of these dyes carries serious threats to living organisms as several dyes and their degradation products are toxic and could be even carcinogenic [4,5]. Therefore, a growing global concern to treat and remove such hazardous has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The release of such materials generates unpleasant colored water as the existence of less than 1 ppm of these dyes in water is highly perceptible. Further, discharge of these dyes carries serious threats to living organisms as several dyes and their degradation products are toxic and could be even carcinogenic [4,5]. Therefore, a growing global concern to treat and remove such hazardous has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Based on previous research theories, ionic MOF materials can adsorb dyes with opposite charges to the pores/channels but dyes that possess same charges will be rejected through ion-exchange and electrostatic interactions. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Liu et al [26] reported an anionic framework material with functional imide groups can efficiently adsorb Basic Red 9 and Basic Violet 14 by electrostatic interaction and ion-exchange. In addition, the adjustable nature of pore structure can allow the window size/shape of MOF materials to match the target dye molecules depend on sizeexclusive effects.…”
Section: Introductionmentioning
confidence: 99%
“…MOF materials exhibit unique advantages in the high adsorption capacity, effective selectivity and rapid adsorption rate of organic pollutants owing to high specific surface area, adjustable pore structure (size, shape and modified functional groups) and designable skeleton structure [12–17] . Based on previous research theories, ionic MOF materials can adsorb dyes with opposite charges to the pores/channels but dyes that possess same charges will be rejected through ion‐exchange and electrostatic interactions [18–36] . Liu et al [26] reported an anionic framework material with functional imide groups can efficiently adsorb Basic Red 9 and Basic Violet 14 by electrostatic interaction and ion‐exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Interpenetration is a well-known structural feature of MOFs, which not only enhances structure stability but also, in comparison to noninterpenetrating frameworks, provides an optimal pore size, thereby improving the adsorption selectivity of the material by restricting the size of the guest molecules entering the pores. Meanwhile, the selection of metal ions and the design of organic ligands as two key roles take part in the construction of stable adsorption and separation materials. According to the hard/soft acid–base principle, the structures constructed by high-oxidation-state metal ions, such as an In 3+ ion, with carboxylic acid ligands tend to give stable MOFs. The introduction of polar functional groups such as amide groups in the ligand can enhance the interaction of the framework with certain guest molecules and further improve the adsorption and separation effects. …”
Section: Introductionmentioning
confidence: 99%